Licensure Examination for Teachers (LET): Reviewer in Professional Education - Salana, June P.; Chavez, Judith C. (Cagayan De Oro, Philippines : IWAG PRINTING AND PUBLISHING, 2006)
This book is designed to help prospective teachers improve their performance in the licensure examination specifically in professional education subjects. This material comprises brief review of salient concepts and test items that would reinforce students' understanding and application or educational theories and constructs.
Theories of development -- Understanding more about learners -- Other related views of learning -- Understanding more about social foundations of education -- Historical foundations of education -- Philosophical foundations of education -- Principles of teaching that adopts the educational -- Models of teacher development -- Lifelong learning -- Four pillars of education -- Multiple intelligences types -- Code of ethics for professional teachers -- Legal bases for philippine education -- More about legal bases for philippine education -- Non-formal education -- Teaching mathematics -- Teaching english -- Teaching makabayan -- Measurement, Evaluation and research.
Includes bibliographical references.
Keywords: EDUCATION -- TEACHING MATERIALS